2014
DOI: 10.1007/978-3-319-07443-6_31
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Common Strategies of Vocabulary Reuse in Linked Open Data Modeling

Abstract: Standard-Nutzungsbedingungen: Dieses Dokument darf zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen dieses Dokument nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, aufführen, vertreiben oder anderweitig nutzen. Sofern für das Dokument eine Open-Content-Lizenz verwendet wurde, so gelten abweichend von diesen Nutzungsbedingungen die in der Lizenz gewährten Nutzungsrechte. Terms of use: This document may be saved and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…The set of features that categorize each recommendation candidate x is enlisted in Table 2. This set of features was derived from [29], which illustrated that the most common strategies and influencing factors to choose a vocabulary terms for reuse is its popularity and whether or not it is from a vocabulary that is already used. Features f1 to f3 represent the popularity of a vocabulary terms whereas feature f4 specifies whether the recommended term is from a vocabulary that is is already used in the query-SLP.…”
Section: Feature Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…The set of features that categorize each recommendation candidate x is enlisted in Table 2. This set of features was derived from [29], which illustrated that the most common strategies and influencing factors to choose a vocabulary terms for reuse is its popularity and whether or not it is from a vocabulary that is already used. Features f1 to f3 represent the popularity of a vocabulary terms whereas feature f4 specifies whether the recommended term is from a vocabulary that is is already used in the query-SLP.…”
Section: Feature Computationmentioning
confidence: 99%
“…(ii) Evaluation of the SLP-feature's impact on the recommendation quality by comparing its recommendations to the baselines of recommending solely popular vocabulary terms and recommending terms from an already used vocabulary [29,24].…”
Section: Introductionmentioning
confidence: 99%
“…Closer to our work, Schaible et al reported on an empirical study involving 75 linked data experts and practitioners assessing reuse strategies based on various ranking decisions [7]. The goal is to find objective criteria for choosing which vocabularies to reuse and how many can be combined.…”
Section: Related Work and Discussionmentioning
confidence: 93%
“…relatively different vocabulary reuse strategies [14]. The two basic forms are  reusing classes and properties from existing vocabularies directly,  establishing links on schema-level, which means defining new classes as either subclasses or equivalent classes and properties as subproperties or equivalent properties of the classes and properties of the reused ontology.…”
Section: B Object and Data Properties Of The Ontologymentioning
confidence: 99%